Chemical cues mediate species recognition in field crickets - Tyler, Frances; Fisher, David; d'Ettorre, Patrizia; Rodríguez-Muñoz, Rolando; Tregenza, Tom (Frontiers in Ecology and Evolution, 2015)
Cuticular hydrocarbons (CHCs) are important in mate choice in many insects, and may be used for species recognition if CHC profiles differ between potentially hybridizing species. In the sibling field cricket species Gryllus campestris and G. bimaculatus, females of G. bimaculatus are tolerant towards G. campestris males and can mate with them. However, G. campestris females are highly aggressive towards heterospecific G. bimaculatus males, and matings between them never happen. We examined whether cricket females might use CHCs to determine the species identity of their potential mates. We firstly analyzed the cuticular chemical profile by gas chromatography and mass spectrometry to assess the potential of CHCs to be used for species recognition in these crickets. We then manipulated females’ ability to detect chemical cues by carrying out chemical ablation of the antennae, and measured changes in aggressive responses to heterospecific males. We show that there are significant interspecies differences in CHC expression for both sexes, and that females with chemically ablated antennae reduce aggressive behavior towards heterospecific males. Our findings support the prediction that cuticular semiochemicals can play a key role in reproductive isolation between closely related insect species.